The Influence of Work Behavior on Employee Performance Through the Work Environment at the Regional Financial and Asset Management Agency of Labuhan Batu Regency - Nugraha, Muhammad Bagus; Lubis, Fajar Rezeki Ananda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The decline in bureaucratic quality is often caused by employees who are less than optimal in carrying out their duties. Therefore, it is important to understand the factors that cause an institution to experience this decline. Therefore, this study will examine the influence of work behavior on employee performance through the work environment at the Regional Finance and Asset Management Agency (BPPA) of Labuhanbatu Regency. This study is expected to answer whether this variable is a contributing factor. Data collection in this study used quantitative methods, and analysis used Structural Equation Modeling (SEM). The study population was all employees at the Regional Finance and Asset Management Agency of Labuhanbatu Regency and related agencies. Data collection in this study involved field observations and questionnaires. The study concluded that work behavior positively influences the work environment. Work behavior also positively influences employee performance. Furthermore, the work environment positively influences employee performance. Finally, work behavior positively influences employee performance through the work environment at the Regional Finance and Asset Management Agency (BPPA) of Labuhanbatu Regency. so it can be concluded that work behavior and work environment need to be maximized in order to achieve maximum performance by each employee at the Regional Finance and Asset Management Agency (BPPA) of Labuhanbatu Regency.